МГУА как инструмент анализа взаимосвязей многомерного процесса - Павлов, Ал.В.; Павлов, Ан.В. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
New approach for complex systems analysis based on discovering of direction impact between processes using self-organizing algorithms is proposed. Input factors filtering, exogenous and endogenous factors sets determining and system processes relationships structure synthesis procedures are offered. Technique proposed makes it possible to reveal possibility of causality sign reversing between processes in the look-ahead period and significantly decrease time of the models system synthesis.